Weed control methods affect weed dynamics, productivity and economics of clusterbean [Cyamopsis tetragonoloba (L.) Taub.] - Rahul; B. R. Meena; Varsha Jeetarwal (Annals of Agricultural Research, 2025)
A field experiment was conducted at Agronomy farm of SKNAU, Jobner during Kharif, 2022 to study the effect of different weed control methods on weed dynamics, growth and yield of clusterbean (Cyamopsis tetragonoloba (L.) Taub.). The experiment was laid out in randomized block design with 10 treatments including unweeded control and weed-free. The results revealed that significantly lower weed density, dry matter production, weed index and higher weed control efficiency were observed under weed free which was followed by Pendimethalin @ 0.75 kg a.i./ha PE + one hand weeding, Pendimethalin @ 0.75 kg a.i./ha PE + Imazethapyr @ 100 g a.i./ha PoE. In majority of the observations related to crop growth, yield attributesand yield attributes, treatment weed-free was found to be at par with Pendimethalin @ 0.75 kg a.i./ha PE + one hand weeding and Pendimethalin @ 0.75 kg a.i./ha PE + Imazethapyr @ 100 g a.i./ha PoE and significantly superior to the rest. Among the different weed control treatments, the maximum net returns ( 70263/ha) and B: C (3.62) was recorded under Pendimethalin @ 0.75 kg a.i./ha PE + one hand weeding which was closely followed by weed-free with 68781/ha net returns and 3.29 B:C ratio over rest of the other treatments.